2015
DOI: 10.1103/physrevd.91.124006
|View full text |Cite
|
Sign up to set email alerts
|

Braneworld solutions for modified theories of gravity with nonconstant curvature

Abstract: We study braneworld models in the presence of scalar field in a five-dimensional geometry with a single extra dimension of infinite extent, with gravity modified to include a function of the Ricci scalar. We develop a procedure that allows to obtain analytical solution for the braneworld configuration in a diversity of models, in the much harder case where the Ricci scalar is non constant quantity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…For a pure geometric theory, we showed that it is impossible to get a smooth version of braneworld model. This is contrary to the metric f (R) theory [43][44][45][46][47]. For the theory with a source field, we used some techniques for the constraints, which can largely simplify the perturbation equations.…”
Section: Discussionmentioning
confidence: 99%
“…For a pure geometric theory, we showed that it is impossible to get a smooth version of braneworld model. This is contrary to the metric f (R) theory [43][44][45][46][47]. For the theory with a source field, we used some techniques for the constraints, which can largely simplify the perturbation equations.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that gravity is not described by general relativity, but by the so-called f (R) theories, where the Lagrangians are proportional to some functions of the scalar curvature R. The f (R) theories were created in the study of cosmology [21][22][23], and they are mainly applied in cosmology nowadays (see [24][25][26][27][28] and references therein). Nevertheless, there are works devoted to embedding branes, either thin [29][30][31][32][33][34], or thick [35][36][37][38][39][40][41][42][43] into various types of f (R) gravities.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain reliable thick f (R)-brane models, we must either prove that the solutions found in Refs. [35][36][37][38][39][40][41][42][43] are also stable against the vector and the scalar perturbations, or to find some new solutions whose stabilities are easier to prove. In this paper we adopt the second path.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This scheme has been dubbed the braneworld scenario. A number of models have been proposed [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] realizing the idea of modeling the brane with a scalar field configuration and the gravitational part of the action is non-minimally coupled to a fundamental or an auxiliary scalar field, as in the case of f (R) gravity. In the present article, we examine 5D models of scalars coupled non-minimally to gravity, in the framework of a frame-invariant formulation and focus on the study of thick braneworld solutions.…”
Section: Introductionmentioning
confidence: 99%